Utilización de la metodología e-learning en el proceso de enseñanza aprendizaje como complemento de la educación presencial del Colegio Nacional Machala del cantón Machala año lectivo 2011 - 2012. - Arriaga Arriaga, Magali Viviana (2012)
In the " Machala " National College , proceeded to do some research on the use of e-learning methodology in the teaching-learning process as a complement to classroom education , this is the place through different techniques : observation, interview and poll. Applying the same results in a high number of teachers know the management of electronic equipment, but at the same time a high percentage of them do not see ICT " s support to help strengthening their classes taught in the classroom. This research also allowed to know what impact positively toward the educational community to the applicability of academic strengthening of the educational institution, through processes , theories, paradigms and pedagogical models applied in education having to train students today .